Teknik “Get Out”, “Let It Out”, dan “Think It Out”: Intervensi regulasi emosi untuk remaja dengan perilaku menyakiti diri - Widiastini, Made Nisa Adriana; Moeliono, Marisa Fransiska (Universitas Muhammadiyah Malang, 2024)
The phenomenon in Indonesia shows the high prevalence of self-harming behavior in teenagers. Self-harm behavior is defined as a form of behavior that involves the destruction of body tissue carried out consciously and deliberately without any desire to end one's life. This research aims to determine the effectiveness of the Get Out,